RANCANG BANGUN ROTARY DRUM BIOREACTOR UNTUK PRODUKSI MICROBIAL CELLULOSE - HARUN SIANTURI; FAJAR RESTUHADI; EVY ROSSI (Universitas Riau, 2016)
Microbial cellulose is the result of bacterial metabolism of Acetobacter xylinum in a liquid medium used. Togrow and produce optimal microbial cellulose, Acetobacter xylinum bacteria requires oxygen for metabolismof glucose. Several studies conducted to obtain optimal results as a static method, RDR, bioreactor dye andspin reactor still has weakness in the tools design. To overcome this weakness a new tool called Rotary DrumBioreactor (RDB) has been created. The design of Rotary Drum Bioreactor particularly aimed to overcomethe weaknesses of the previous studies and to determine the best treatment using RDB in better producing ofmicrobial cellulose. The study started on the selection tools and materials that will be used in designing theRDB tools, then proceed to design the tools to be able to work with four tools simultaneously that havedifferent speeds in each fermentor including 2, 4,6 and 8 rpm, as the treatment with three replications anduntreated comparison is static fermentation. The third phase was testing tools in producing microbialcellulose and then the data were analyzed statistically using analysis of variance followed by further test ofDuncan’s New Multiple Range Test (DNMRT) at 5% level. The analysis showed that the speed of 2 rpm for 6days of fermentation gave the best results including 95.02% moisture content, wet weight of 0.62 gr/ cm2 andyield 9.92%.